Correlates of socio-economic inequalities in women's television viewing: a study of intrapersonal, social and environmental mediators - Teychenne Megan; Ball Kylie; Salmon Jo (BMC, 2012)
Abstract Introduction Socio-economically disadvantaged women are at a greater risk of spending excess time engaged in television viewing, a behavior linked to several adverse health outcomes. However, the factors which explain socio-economic differences in television viewing are unknown. This study aimed to investigate the contribution of intrapersonal, social and environmental factors to mediating socio-economic (educational) inequalities in women's television viewing. Methods Cross-sectional data were provided by 1,554 women (aged 18-65) who participated in the 'Socio-economic Status and Activity in Women study' of 2004. Based on an ecological framework, women self-reported their socio-economic position (highest education level), television viewing, as well as a number of potential intrapersonal (enjoyment of television viewing, preference for leisure-time sedentary behavior, depression, stress, weight status), social (social participation, interpersonal trust, social cohesion, social support for physical activity from friends and from family) and physical activity environmental factors (safety, aesthetics, distance to places of interest, and distance to physical activity facilities). Results Multiple mediating analyses showed that two intrapersonal factors (enjoyment of television viewing and weight status) and two social factors (social cohesion and social support from friends for physical activity) partly explained the educational inequalities in women's television viewing. No physical activity environmental factors mediated educational variations in television viewing. Conclusions Acknowledging the cross-sectional nature of this study, these findings suggest that health promotion interventions aimed at reducing educational inequalities in television viewing should focus on intrapersonal and social strategies, particularly providing enjoyable alternatives to television viewing, weight-loss/management information, increasing social cohesion in the neighborhood and promoting friend support for activity.